PELAKSANAAN PEMBELAJARAN BLENDED LEARNING DALAM PEMBELAJARAN BAHASA INDONESIA KELAS VII SMPN 23 PONTIANAK - Musyarrofah, Musyarrofah; Syam, Christanto; Lasmono, Djon (Universitas Tanjungpura, 2024)
This study aims to determine the character of the responsibility of students in economic learning at SMA Santun Untan Pontianak. The research method used is descriptive qualitative.research method. The source of the research data was one teacher and 5 students from SMA Santun Untan Pontianak. The data collection techniques used were observation and interviews. Data analysis techniques used are collection, reduction, display, and drawing conclusions. The results of this study indicate that there are some students who still do not have a good character of responsibility, there are still many who do not do the task optimally, there are still many who have not been able to do their own work, there is still no awareness in themselves about their responsibilities as students. The teacher uses two ways to apply the responsible character of students in economic learning, namely in the form of praise (motivation), and in the form of sanctions to provide a deterrent effect on students who do not have the character of responsibility well. students do not get bored quickly with the material explained to students.